P PELAKSANAAN TIMBANG TERIMA MENGGUNAKAN KOMUNIKASI SBAR PADA PROSES TRANSFER PASIEN KE RUANG PERAWATAN UNTUK TENAGA KESEHATAN: NARATIVE REVIEW - puspa ayu devira (Journal of Nursing Invention, 2021)
Background: Unexpected events (KTD) occur due to delayed communication. This can be prevented by using effective communication. Effective communication is also a major component of providing good nursing care services according to patient needs. One form of effective communication is the SBAR method. SBAR communication consists of 4 components, namely S (situation), B (Background), A (Assessment), and R (Recommendation). Objective: This study aims to evaluate the implementation of handover using sbar communication in the process of transferring patients to care rooms for health workers. Methods: This study used a narrative review approach. Narative review identified through a search on the Google Scholar, DOAJ, Biomed Central database and obtained 10 journals that match the inclusion criteria. Results: The results of this narrative review indicate that the implementation of SBAR communication experienced obstacles such as the urgent situation and the rush of the handover process, differences in perceptions between SBAR users, the burden of demands, and the pattern of SBAR implementation between nurses and other health workers. Conclusion: The implementation of SBAR in handover during the patient transfer process was carried out quite well, but not maximally, this was because health workers still feel less motivated to carry out SBAR communication and there were still differences in perceptions among health workers. The implementation of this SBAR forms a pattern for its used, both among nurses, nurses and doctors, nurses and pharmacies and others.